2020
DOI: 10.1159/000510652
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Care for Patients with Inflammatory Bowel Disease: Japanese Experience

Abstract: <b><i>Background:</i></b> Transition-related healthcare intervention has recently been receiving worldwide attention. Given the increasing incidence of pediatric inflammatory bowel disease (IBD) and its lifelong impact, transitional care has become an important issue. In Japan, guidelines to support the autonomy of IBD patients during transition were recently published. <b><i>Summary:</i></b> Here, we review current issues regarding care for IBD patients during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Many previous studies have identified various barriers to the seamless transfer of IBD care 16 . For caregivers, high parental involvement and underestimation of the child's capability are barriers to successful transition.…”
Section: Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…Many previous studies have identified various barriers to the seamless transfer of IBD care 16 . For caregivers, high parental involvement and underestimation of the child's capability are barriers to successful transition.…”
Section: Statementmentioning
confidence: 99%
“…Adult care is patient‐focused and investigational, requiring autonomous, independent consumer skills without many interdisciplinary resources 23 . The cultural difference between the two health‐care providers can be a barrier to successful transition 16 . Through discussion with patients and their families about the future, pediatric health‐care providers should provide information about adult care services to patients, and make them aware that they will live their lives in the adult medical world.…”
Section: Statementmentioning
confidence: 99%
See 3 more Smart Citations